Peran Pemimpin dalam Membangun Motivasi Kerja Karyawan di Tengah Persaingan Industri Rajut - Teofadli Mubaroq; Agus Alamsyah (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This research aims to understand the role of leaders in building employee work motivation at CV Saung Rajut, particularly in the context of fierce competition in the knitting industry. As the industry constantly evolves, effective leadership becomes crucial for improving employee morale, loyalty, and productivity. This study uses a qualitative approach with data collection techniques including interviews, observations, and documentation. The findings indicate that the leader at CV Saung Rajut has successfully created a conducive and harmonious work environment. Leaders position employees as partners, lead by example, and foster humanistic and empathetic communication. These actions motivate employees to innovate and make deeper contributions toward achieving the company’s goals, demonstrating the impact of transformational leadership. Additionally, the company’s flexible work system and family-oriented work culture further strengthen both intrinsic and extrinsic motivation among employees. The research highlights that leadership at CV Saung Rajut goes beyond traditional methods, creating a work atmosphere that promotes collaboration, trust, and commitment. This, in turn, supports the company’s competitiveness in the industry. Effective leadership not only boosts employee engagement but also contributes to the overall success and sustainability of the company in a highly competitive market.